2022
DOI: 10.1128/iai.00414-22
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutations in TbpA Abrogate Human Transferrin Binding in Neisseria gonorrhoeae

Abstract: TonB-dependent transporters (TDTs) are essential proteins for metal acquisition, an important step in the growth and pathogenesis of many pathogens, including Neisseria gonorrhoeae , the causative agent of gonorrhea. There is currently no available vaccine for gonorrhea; TDTs are being investigated as vaccine candidates because they are highly conserved and expressed in vivo .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…This region could have a significant role in the interaction of HpuB with hHb, and in ensuring heme extraction from Hb as seen previously with loop 3 helices of both TbpA and TdfJ (43,62,63). Therefore, acquiring a highresolution structure of HpuB, either by protein x-ray crystallography or cryo-electron microcopy, will help better inform the choice of future mutational targets on the extracellular loops as in other studies (43,62,63). As previously published, Transferrin-Binding Protein B (TbpB) and factor H binding protein (fHbp) mutants that are unable to bind host ligands demonstrated better vaccine potential (33)(34)(35).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This region could have a significant role in the interaction of HpuB with hHb, and in ensuring heme extraction from Hb as seen previously with loop 3 helices of both TbpA and TdfJ (43,62,63). Therefore, acquiring a highresolution structure of HpuB, either by protein x-ray crystallography or cryo-electron microcopy, will help better inform the choice of future mutational targets on the extracellular loops as in other studies (43,62,63). As previously published, Transferrin-Binding Protein B (TbpB) and factor H binding protein (fHbp) mutants that are unable to bind host ligands demonstrated better vaccine potential (33)(34)(35).…”
Section: Discussionmentioning
confidence: 79%
“…We demonstrated the importance of residues 538-544 which constitute a hypothetical α-helical region in loop 7. This region could have a significant role in the interaction of HpuB with hHb, and in ensuring heme extraction from Hb as seen previously with loop 3 helices of both TbpA and TdfJ (43,62,63). Therefore, acquiring a highresolution structure of HpuB, either by protein x-ray crystallography or cryo-electron microcopy, will help better inform the choice of future mutational targets on the extracellular loops as in other studies (43,62,63).…”
Section: Discussionmentioning
confidence: 85%
“…Finney et al showed that antibodies against these proteins can protect against Neisseria lactamica meningococcal infection in rabbits (Finney et al, 2008). The TBDR transporter of Neisseria gonorrhoeae, i.e., TbpB, has also been targeted for vaccine design, in addition to TbpA, and shown to invoke an immune response in mice (Greenawalt, 2021). Additionally, several vaccine candidates Frontiers in Molecular Biosciences frontiersin.org targeting TBDRs have been developed for various bacterial pathogens, including Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumonia (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The prototype system in N. gonorrhoeae is the transferrin receptor, comprised of the TbpA transporter and the TbpB lipoprotein that increases the affinity of TbpA for transferrin. Structural analysis of TbpA co-crystalized with human transferrin reveals the helix finger of TbpA directly extends within a cleft on the C-lobe of human transferrin to extract iron [19,20]. The outer membrane receptors are energized by the proton motive force harnessed by TonB, ExbB, and ExbD, which pull on the "plug domain" to physically open each receptor to enable transport; hence, they are collectively known as "Tdfs," for TonB-dependent family members.…”
Section: How Does N Gonorrhoeae Use Outer Membrane Receptors For Huma...mentioning
confidence: 99%